Genetic evolution of T-cell resistance in the course of melanoma progression - Sucker, Antje; Kloor, Matthias; Schadendorf, Dirk (Clinical cancer research, 2014)
Purpose: CD8+ T lymphocytes can kill autologous melanoma cells, but their activity is impaired when poorly immunogenic tumor phenotypes evolve in the course of disease progression. Here, we analyzed three consecutive melanoma lesions obtained within one year of developing stage IV disease for their recognition by autologous T cells. - Experimental Design: One skin (Ma-Mel-48a) and two lymph node (Ma-Mel-48b, Ma-Mel-48c) metastases were analyzed for T-cell infiltration. Melanoma cell lines established from the respective lesions were characterized, determining the T-cell-stimulatory capacity, expression of surface molecules involved in T-cell activation, and specific genetic alterations affecting the tumor-T-cell interaction. - Results: Metastases Ma-Mel-48a and Ma-Mel-48b, in contrast with Ma-Mel-48c, were infiltrated by T cells. The T-cell-stimulatory capacity was found to be strong for Ma-Mel-48a, lower for Ma-Mel-48b, and completely abrogated for Ma-Mel-48c cells. The latter proved to be HLA class I-negative due to an inactivating mutation in one allele of the beta-2-microglobulin (B2M) gene and concomitant loss of the other allele by a deletion on chromosome 15q. The same deletion was already present in Ma-Mel-48a and Ma-Mel-48b cells, pointing to an early acquired genetic event predisposing to development of β2m deficiency. Notably, the same chronology of genetic alterations was also observed in a second β2m-deficient melanoma model. - Conclusion: Our study reveals a progressive loss in melanoma immunogenicity during the course of metastatic disease. The genetic evolvement of T-cell resistance suggests screening tumors for genetic alterations affecting immunogenicity could be clinically relevant in terms of predicting patient responses to T-cell-based immunotherapy. Clin Cancer Res; 20(24); 6593-604. ©2014 AACR.